2022
DOI: 10.3390/diseases10010009
|View full text |Cite
|
Sign up to set email alerts
|

D-Amino Acids as a Biomarker in Schizophrenia

Abstract: D-amino acids may play key roles for specific physiological functions in different organs including the brain. Importantly, D-amino acids have been detected in several neurological disorders such as schizophrenia, amyotrophic lateral sclerosis, and age-related disorders, reflecting the disease conditions. Relationships between D-amino acids and neurophysiology may involve the significant contribution of D-Serine or D-Aspartate to the synaptic function, including neurotransmission and synaptic plasticity. Gut-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 110 publications
0
11
0
Order By: Relevance
“…A brief introduction Schizophrenia is a significant cause of disability with varied causes, and gut microbiome has been linked to its development [45][46][47][48][49][50] Depression is a prevalent cause of disability worldwide, with the gut microbiome being implicated in its pathogenesis [60][61][62] Generalized anxiety disorder (GAD) is a prevalent and enduring type of anxiety, affecting 4%-6% of the total population [70] Autism spectrum disorder (ASD) is a neurodevelopmental condition that affects social interaction and communication and is typically identified in early childhood [1,5,77,78] Neurotransmitters involved in the mental disorders Impairment in the tryptophan to serotonin conversion pathway is plausibly linked to schizophrenia [9] Researchers suggest that d-serine could be associated with schizophrenia [54,57] The role of GABAergic transmission in schizophrenia has recently risen in significance [54] Tryptophan and Serotonin are centrally involved in the pathogenesis of depression [9] Modifying dopamine levels may have therapeutic applications for depression [21] GABA has been associated with treating depression [31] Glutamatergic signaling has been linked to depression [42,44] Tryptophan and serotonin also play a crucial role in the pathogenesis of anxiety [9] Modifying dopamine levels can have therapeutic applications for anxiety [21] GABA can also reduce anxiety [31] Modifying dopamine levels can have therapeutic applications on autism [21] Glutamate metabolization may be linked to autism [38,42] Microbiota effect on the neurotransmitters -Numerous bacterial species have reportedly expressed serotonin-synthesizing properties [14] -Gut commensal strains Lactobacillus and Bifidobacterium have been found able to produce GABA [54] -Altering gut microbial may modify the metabolism of d-amino acids…”
Section: Schizophrenia Depression Anxiety Disorder Autism Spectrum Di...mentioning
confidence: 99%
“…A brief introduction Schizophrenia is a significant cause of disability with varied causes, and gut microbiome has been linked to its development [45][46][47][48][49][50] Depression is a prevalent cause of disability worldwide, with the gut microbiome being implicated in its pathogenesis [60][61][62] Generalized anxiety disorder (GAD) is a prevalent and enduring type of anxiety, affecting 4%-6% of the total population [70] Autism spectrum disorder (ASD) is a neurodevelopmental condition that affects social interaction and communication and is typically identified in early childhood [1,5,77,78] Neurotransmitters involved in the mental disorders Impairment in the tryptophan to serotonin conversion pathway is plausibly linked to schizophrenia [9] Researchers suggest that d-serine could be associated with schizophrenia [54,57] The role of GABAergic transmission in schizophrenia has recently risen in significance [54] Tryptophan and Serotonin are centrally involved in the pathogenesis of depression [9] Modifying dopamine levels may have therapeutic applications for depression [21] GABA has been associated with treating depression [31] Glutamatergic signaling has been linked to depression [42,44] Tryptophan and serotonin also play a crucial role in the pathogenesis of anxiety [9] Modifying dopamine levels can have therapeutic applications for anxiety [21] GABA can also reduce anxiety [31] Modifying dopamine levels can have therapeutic applications on autism [21] Glutamate metabolization may be linked to autism [38,42] Microbiota effect on the neurotransmitters -Numerous bacterial species have reportedly expressed serotonin-synthesizing properties [14] -Gut commensal strains Lactobacillus and Bifidobacterium have been found able to produce GABA [54] -Altering gut microbial may modify the metabolism of d-amino acids…”
Section: Schizophrenia Depression Anxiety Disorder Autism Spectrum Di...mentioning
confidence: 99%
“…In this way, they influence neuronal development and brain mitochondrial dynamics. One positive pathway related to a “healthy” microbiome is via the production of SCFA that can upregulate PGC-1α as a master regulator of mitochondrial biogenesis ( Petra et al, 2015 ; Bastings et al, 2019 ; Kobayashi, 2019 ; Theunissen et al, 2021 ; Taniguchi et al, 2022 ). Strategies to enhance melatonin production and or exogenous delivery are described in PART III.…”
Section: Part Ii: Mitochondrial Dysfunction and Its Involvement In Di...mentioning
confidence: 99%
“…Preclinical studies in an animal model of Sch have demonstrated that a decrease in the level of D-Ser in the CNS due to a decrease in SR activity can cause Sch symptoms, including stereotypy, cognitive impairment, impaired prepulse inhibition (a measure of sensorimotor gating), persistent latent inhibition (a measure of inhibition of learning and cognitive flexibility) and a lack of social interaction [ 38 , 96 , 97 ].…”
Section: D-serinementioning
confidence: 99%